Accelerate energy transition with smarter regulation for faster grid digitalization - Marques, V. (2021)
This paper aims to improve the understanding about the most appropriate regulatory approaches to incentivize the adoption of the new technology innovations needed to modernize the distribution networks and enable the energy transition. There is a large set of new technologies, such as technologies related to advanced metering infrastructure (smart metering and communication), substation and feeder automation and low voltage microgrids, which have positive externalities, going beyond the provision of basic network activities or the improvement of quality of service. These externalities have a value for the grid that needs to be accounted for, challenging traditional regulatory models, which tend to overlook the indirect benefits of investments. We characterize a group of representative innovative investments in the grid, considering their expected gains and functionalities that namely enable the development of new services and reinforce efficiency and resilience, while preserving the social and economic affordability. Then, we develop a decision model, which assesses the changes in the firms’ incentives to invest in new technologies under different regulatory schemes. Two representative regulatory settings have been compared: TOTEX; and hybrid regulatory schemes. We compare this model with the profile of the different types of innovations under survey. The results show that a TOTEX regulatory scheme, which fully emulates a competitive situation, more effectively promotes innovative investments or processes that bring benefits in reducing total network costs than cost plus or other regulatory schemes. This result is still valid if the innovative technology lead to an increase in OPEX, provided that total costs decrease. However, for technologies, whose benefits go beyond the network activities, the results show that there is no a one size fit all regulatory scheme, and a case-by-case approach should be preferred.